Occurrence of Isopods in Two Species of Snappers (Lutjanidae) from Northeast Brazil - André M. Alves; Marina G. Leonardo; Geza T. R. Souza; Ricardo M. Takemoto; Flávia S. de Lima; Luiz E. R. Tavares; Cláudia M. Melo; Rubens R. Madi; Verónica L. S. Jeraldo (Journal of Parasitology Research)
Parasitic isopod species are poorly known in the northeastern coast of Brazil. In this sense, this study presents novel records of Isopoda of the families Aegidae, Cymothoidae, and Corallanidae. A total 69 specimens of Lutjanus analis and 19 of Lutjanus jocu, of which 46 isopods from 3 different species were collected, i.e. Rocinela signata, Cymothoa excisa, and Excorallana richardsoni. The species R. siganata and E. richardsoni are reported for the first time in L. jocu. A significant relationship between the parasite R. signata and the size of the fish L. jocu was also observed. The isopod C. excisa is considered an incidental finding in L. analis. To the authors’ knowledge, this is the first report of this species in fish from Brazil. The three species of isopods are new occurrences in the State of Sergipe, northeast region of the country. An additional morphological characteristic observed in the dorsal setae of pleotelson in specimens of E. richardsoni was that one end of this structure wws bifid. This information contributes to the current body of knowledge of the morphology of this particular species.